2016
DOI: 10.1111/1754-9485.12565
|View full text |Cite
|
Sign up to set email alerts
|

Value of18F‐FDG PET/MRIfor the outcome ofCT‐guided facet block therapy in cervical facet syndrome: initial results

Abstract: F-FDG PET/MRI can detect PET-positive cervical facet arthropathy and help to identify patients benefitting from facet block therapy. Bone marrow TIRM SI ratio might be a surrogate for PET-positive facet arthropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…54 69 Finally, a small retrospective study performed in 10 patients with chronic neck pain sought to determine whether positron emission tomography (PET)/MRI could be used to identify patients for therapeutic cervical MBB performed with high volumes of LA and steroid. 70 Increased 18F-fluoro-deoxyglucose uptake along with facet arthrosis was observed in six joints in six patients. These patients exhibited better pain relief 3 hours after the blocks, which persisted through 3-month follow-up.…”
Section: Mri Therapeutic Facet Injections and Radiofrequency Denervationmentioning
confidence: 89%
“…54 69 Finally, a small retrospective study performed in 10 patients with chronic neck pain sought to determine whether positron emission tomography (PET)/MRI could be used to identify patients for therapeutic cervical MBB performed with high volumes of LA and steroid. 70 Increased 18F-fluoro-deoxyglucose uptake along with facet arthrosis was observed in six joints in six patients. These patients exhibited better pain relief 3 hours after the blocks, which persisted through 3-month follow-up.…”
Section: Mri Therapeutic Facet Injections and Radiofrequency Denervationmentioning
confidence: 89%
“…The correlation of back pain and imaging findings was not otherwise reported, and clinically implicated facet joints were not determined. 6 Sawicki et al 14 reported that FDG-PET/MR imaging-directed cervical facet joint steroid injections were associated with improved clinical pain scores relative to clinically selected facet joints in patients without imaging findings positive for increased activity, though MBBs were not used and gadolinium was not administered. They also found that MR imaging T2 hyperintensity and FDG activity may be surrogates.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that MR imaging T2 hyperintensity and FDG activity may be surrogates. 14 One prior study suggested that FDG-PET/MR imaging findings of the lumbar spine may help identify various causes of sciatica, including inflamed facet joints. 19 Limited evidence indicates that muscular or nerve FDG activity may be present in a painful lower extremity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 F-FDG PET also appeared useful as guidance for therapy in patients with cervical facet syndrome. In a study involving 140 facet joints, 100% concordance was found between location of focal 18 F-FDG uptake and painful area in the neck (33).…”
Section: Non-oncologic Pet Imaging Of Head and Neckmentioning
confidence: 99%